Self-assessment of academic achievements in the examination situation and personality traits of students of the youth age period - Aleksandr A. Baranov; Olga N. Malakhova; Olga A. Zhuchenko (Saratov State University, 2023)
The study presents the results of the correlation between students' predictive competence and their personal characteristics. The relevance and novelty of the research results are attributed to the specification of the problematic issue connected with predictive competence. The latter is determined through the students' subjective characteristics which are associated with self-assessment of academic achievements in the examination situation. The developed predictive competence is one of the acmeological invariants of professionalism and a resource that increases stress resistance. The aim of the research is to study the correlation between personality traits of students of the youth age period and the adequacy of their self-assessment of the academic achievements in a stressful examination situation. The study hypothesizes that personal characteristics of students determine the adequacy level of their self-assessment of the academic results and reduce the level of examination stress. The sample of the study comprises 287 first- and second-year students of the youth age period, majoring in natural sciences and socio-economic educational areas and specialties of Udmurt State Agrarian University (Izhevsk) (their average age is 18.5; 45% are girls, 55% are boys). The methods (tools) of the research are as follows: in order to fix the components of self-assessment of academic achievements and the level of mental tension of young people in the examination situation, the authors used the Dembo - Rubinstein technique (in the original modification); to determine the features of predictive skills, the "Anticipatory Consistency Test" developed by V. D. Mendelevich (ACT) was used; to measure the manifestations of anxiety as a personal quality that affects the stress level during examinations, the "The Taylor Manifest Anxiety Scale" was applied (adapted by T. A. Nemchin, V. G. Noskaridze), to measure the level of the control locus the "Rotter's Locus of Control Scale" (adapted by E. F. Bazhin, E. A. Golynkina, A. M. Etkind) was used. The study results. Positive correlation between the locus of control and personal anxiety and negative cor- relation between the predictive competence and situational tension are characteristic of students with an adequate self-assessment of academic achievements. Developed predictive competence reduces the exam stress. The conclusion. Adequate self-assessment of academic achievements in a stressful situation contributes to the management of one's own activities and to a better manifestation of competencies while performing intellectual tests. The obtained results are used to improve the personality-oriented program for the development of adequate self-assessment of academic achievements which serves as a stress resistance resource of students of the youth age period.